INFLUENCE EPOXIDE-CONTAINING POLYOXYPROPYLENE TRIOLS ON THE GENETIC APPARATUS IN A LONG TOXIFICATION IN SMALL DOSES - Zhukov, V.I.; Scherban, N.G.; Nikolaeva, O.V.; Kucheriavchenko, M.A. (World of Medicine and Biology, 2015)
The pollution of environmental objects - industrial, municipal, domestic, natural chemicals in the period of scientific and technological progress poses a growing threat to public health. Many chemical compounds polluting the human environment can have on the body of the specific effect, which manifests itself not in the period of exposure and immediately after its completion and to remote periods in the life of the individual. Even more significant for the society is the manifestation of the adverse effects caused by chemical in subsequent generations. As objects of research a group Laproxides was chosen, that found wide application in different industries of national economy for the receipt of epoxide-containing resins, plastics, varnishes, enamels of and other with the regulated physicochemical properties. Were in-process used: triglycidyl ether of polyoxypropylene triol with molecular mass 300 (L- 303); 500 (L- 503); 700 (L- 703) and oligo ether of monoepoxides with molecular mass 500 (L- 512). The aim of the work was to study the effect of Laproxides in conditions of prolonged sub-toxic intake of experimental animals in the genetic apparatus and justification of forecast potential danger to humans and the environment. The experiment was conducted on white adult Wistar rats weighing 190-205 g, which were subjected to a daily oral exposure to aqueous solutions of xenobiotics at the rate of 1/10, 1/100 and 1/1000 DL50. Prolonged exposure was 2.5 months. The research program includes the study of mutagenic activity Laproxides on cells of bone marrow with high mitotic activity. Two hours prior to decapitation of the animal was administered intraperitoneally 2.5 mg / kg of colchicine. Preparations bone marrow were prepared by the standard technique with subsequent staining Romanovsky-Giemsa. From each rat was analyzed on 100 metaphases. We take into account the single and paired fragments, translocations, dicentric, deletions, ring chromosomes, spaces are not taken into account. The bone marrow cell preparations were calculated dividing cells at 1500 cells for each animal. Specifies the number of cells with aberrations and mitotic index. To identify the dominant lethal mutations were used males who were toxification Laproxides over the full cycle of spermatogenesis (2,5 months.). Fertilization intact females were performed by males who were exposed to sub-toxic 1/10 DL50 test substances, the most important dose effects in subacute experiment. On detection of sperm in vaginal smears, pregnancy was considered. On the 20th day of pregnancy were calculated overall, pre-implantation and post implantation death of embryos. The findings suggest that Laproxides in the dose of 1/10 and 1/100 DL50 increase the frequency of chromosomal aberrations in the form of deletions, dicentric, translocations, single and paired fragments, ring chromosomes and reduce the mitotic activity of the cells of bone marrow. The 1/10 DL50 xenobiotics reduce the number of live embryos and increase the number of places resorption, with increased pre-implantation, post-implantation and general fetal death. Manifestation mutagenic effect at the level of general toxic action allowed to exclude them from this group of compounds the presence of specific mutagenic action.